Aspects of the blood meal of mosquitoes (Diptera: culicidae) during the crepuscular period in Atlantic Forest remnants of the state of Rio de Janeiro, Brazil - Alves, Dálete Cássia Vieira; Machado, Sérgio Lisboa; Silva, Júlia dos Santos; de Almeida, Nathália Menezes; Dias, Rayane; Silva, Shayenne Olsson Freitas; Alencar, Jeronimo (Frontiers in Ecology and Evolution, 2026)
Identifying their food sources provides insights into mosquito foraging behaviors and directly impacts the epidemiology of mosquito-borne pathogens such as dengue, Zika, and chikungunya. Understanding these feeding patterns becomes even more relevant in ecosystems like the Atlantic Forest, where biodiversity is rich and complex. The present study was conducted in Atlantic Forest remnants of the Guapiaçu Ecological Reserve (REGUA) and the Sítio Recanto Preservar, both located in the state of Rio de Janeiro, Brazil. We aimed to identify the food sources of mosquitoes present in these areas, contributing to a better understanding of ecological and epidemiological dynamics. Molecular techniques, such as Sanger DNA sequencing of cytochrome b (Cytb), allows for precise identification of food sources, which is fundamental for designing control and monitoring strategies for mosquito populations. A total of 1,714 mosquitoes were captured, of which only 145 females (6.98%) were engorged. The results revealed a clear tendency for the captured mosquito species to feed predominantly on humans. Additionally, we emphasize the need to continuously improve techniques to identify food sources, aiming to better understand interactions between mosquitoes and their environment. This information is crucial for developing effective policies and strategies to control vector-borne pathogens.